Microcatheter-guided compartment packing of acutely ruptured complex intracerebral aneurysms (ARCIAs): Preliminary experience and technical note - Zhang, Yi-Bin; Xie, Bing-Sen; Wang, Hao-Jie; Huang, Sheng-Xuan; Fan, Wen-Jian; Zhu, Mei; Chen, Guo-Rong; Wang, Deng-Liang; Yao, Pei-Sen; Yu, Liang-Hong; Dai, Lin-Sun; Kang, De-Zhi; et al. (Frontiers in Neurology, 2022)
Objective We present our initial experience using the microcatheter-guided compartment packing (MCP) technique for endovascular embolization of acutely ruptured complex intracerebral aneurysms (ARCIAs) and evaluate the safety, feasibility, and efficiency of this technique. Methods This retrospective, single-center study included 28 patients who underwent coil embolization using the MCP technique for ARCIAs at our institution between January 2021 and January 2022. The MCP technique was the placement of microcatheters in different compartments within the aneurysm to deploy the coils simultaneously or sequentially. Patient demographics, aneurysm characteristics, procedural parameters, grade of occlusion, complications, and clinical results were analyzed. The clinical outcomes were evaluated with modified Rankin Scale (mRS) scores. Results Of the 28 patients successfully treated with the MCP technique, 24 (85.7%) aneurysms were considered as complete occlusions (Raymond I) based on the immediate postembolization angiogram results. Complications occurred in 2/28 treatments, including guidewire perforation with subarachnoid hemorrhage and cerebral vasospasm-related cerebral infarction. An angiography follow-up demonstrated complete occlusion in 25/28 aneurysms. Twenty-six (92.9%) patients had favorable 90-day outcomes (mRS 0-2) after the endovascular coil embolization. Conclusion The MCP technique is simple, safe, and effective, achieving good packing density and initial occlusion rate when used to treat ARCIAs.